Excel for chemists : a comprehensive guide - Billo, E. Joseph (Hoboken, N.J. : Wiley, 2011)
'Chemists across all subdisciplines use Excel to record data in tabular form, but few have learned to take full advantage of the program. Featuring clear step-by-step instructions, Excel for Chemists illustrates how to use the scientific calculating power of Excel to perform a variety of chemical, biochemical, physical, engineering, biological, and medicinal calculations. Including a CD-ROM for Windows, this new edition provides chemists and students with the a detailed guide to using the current versions of Excel (Excel 2007 and 2010), Excel 2003, as well as many other new applications. A wide range of methods is described, including creating advanced spreadsheet formulas to using Excel's built-in functions and tools, to creating advanced macros using Excel's Visual Basic.'--Provided by publisher.
PART I THE BASICS -- Chapter 1 Working with Excel 2007 or Excel 2010 -- Chapter 2 Working with Excel 2003 -- Chapter 3 Excel Formulas and Functions -- Chapter 4 Excel 2007/2010 Charts -- Chapter 5 Excel 2003 Charts -- PART II ADVANCED SPREADSHEET TOPICS -- Chapter 6 Advanced Worksheet Formulas -- Chapter 7 Array Formulas -- Chapter 8 Advanced Charting Techniques -- Chapter 9 Using Excel's Database Features -- Chapter 10 Importing Data into Excel -- Chapter 11 Adding Controls to a Spreadsheet -- Chapter 12 Other Language Versions of Excel -- PART III SPREADSHEET MATHEMATICS -- Chapter 13 Mathematical Methods for Spreadsheet Calculations -- Chapter 14 Linear Regression and Curve Fitting -- Chapter 15 Nonlinear Regression Using the Solver -- PART IV EXCEL'S VISUAL BASIC FOR APPLICATIONS -- Chapter 16 Visual Basic for Applications: An Introduction -- Chapter 17 Programming with VBA -- Chapter 18 Working with Arrays in VBA -- PART V SOME APPLICATIONS OF VBA -- Chapter 19 Command Macros -- Chapter 20 Custom Functions -- Chapter 21 Automatic Procedures -- Chapter 22 Custom Menus -- Chapter 23 Custom Toolbars and Toolbuttons -- PART VI APPENDICES -- Appendix A What's Where in Excel 2007/2010 -- Appendix B Selected Worksheet Functions by Category -- Appendix C Alphabetical List of Selected Worksheet Functions -- Appendix D Renamed Functions in Excel 2010 -- Appendix E Selected Visual Basic Keywords by Category -- Appendix F Alphabetical List of Selected Visual Basic Keywords -- Appendix G Selected Excel 4 Macro Functions -- Appendix H Shortcut Keys by Keystroke -- Appendix I Selected Shortcut Keys by Category -- Appendix J ASCII Codes -- Appendix K Contents of the CD-ROM.
'The accompanying CD contains a number of Excel macros to facilitate chemical calculations, including molecular weight, nonlinear regression statistics, and data interpolation'--P. [4] of cover.
Includes index.
Book is accompanied by one CD entittled' Excel for chemists : a comprehensive guide' bearing the same call number at Bahagian Koleksi Media.
System requirements for CD-ROM: Windows, most workbooks are in 2003 format (.xls) and can be read by users with Excel 97/2000/2003 or Excel 2007/1010.
Keywords: Microsoft Excel (Computer file).; Chemistry -- Data processing; Electronic spreadsheets